Chapter Power, Patronage, and Confessionalism Ottoman Politics as Seen through the Eyes of a Crimean Sufi, 1580-1593 - Terzioglu, Derin (Crete University Press, 2019)
The present article aims to contribute to a more nuanced understanding of both the politics of Sufism and the practice of politics in the Ottoman Empire in the late sixteenth century through a contextual study of the collection of letters written by the Halveti sheikh İbrahim-i Kırımî (d. 1593) to Murad III (r. 1574-1595).